2016
DOI: 10.1186/s40478-016-0291-x
|View full text |Cite
|
Sign up to set email alerts
|

C1q-targeted inhibition of the classical complement pathway prevents injury in a novel mouse model of acute motor axonal neuropathy

Abstract: IntroductionGuillain-Barré syndrome (GBS) is an autoimmune disease that results in acute paralysis through inflammatory attack on peripheral nerves, and currently has limited, non-specific treatment options. The pathogenesis of the acute motor axonal neuropathy (AMAN) variant is mediated by complement-fixing anti-ganglioside antibodies that directly bind and injure the axon at sites of vulnerability such as nodes of Ranvier and nerve terminals. Consequently, the complement cascade is an attractive target to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 40 publications
3
59
0
Order By: Relevance
“…Annexon Biosciences ( http://www.annexonbio.com/science/ ) have developed C1q-blocking monoclonal antibodies (ANX005/007) for therapy of AD but have not yet addressed the delivery problem. Another anti-C1q antibody was neuroprotective in a mouse peripheral neuropathy model [ 90 ]. Numerous small-molecule anti-complement drugs targeting complement receptors (for example, C5a receptor antagonist peptides; [ 91 ]) or complement enzymes (for example, factor D blockers; [ 92 ]) are in development and approaching the clinic; however, to date, none have been designed with BBB penetrance in mind.…”
Section: Targeting Complement In Admentioning
confidence: 99%
“…Annexon Biosciences ( http://www.annexonbio.com/science/ ) have developed C1q-blocking monoclonal antibodies (ANX005/007) for therapy of AD but have not yet addressed the delivery problem. Another anti-C1q antibody was neuroprotective in a mouse peripheral neuropathy model [ 90 ]. Numerous small-molecule anti-complement drugs targeting complement receptors (for example, C5a receptor antagonist peptides; [ 91 ]) or complement enzymes (for example, factor D blockers; [ 92 ]) are in development and approaching the clinic; however, to date, none have been designed with BBB penetrance in mind.…”
Section: Targeting Complement In Admentioning
confidence: 99%
“…shown to be impaired in neurodegenerative conditions where microglia can be dysfunctional and/or excessive synaptic pruning might take place [23][24][25][26][27]. To visualize microglial activation in vivo[ 5 9 8 _ T D $ D I F F ] , positron emission tomography (PET) imaging has been employed in human AD studies [28][29][30][31].…”
Section: Trem2: Presenting Microglia Front and Center In Admentioning
confidence: 99%
“…In summary, many collaborative efforts have demonstrated that anti-GM1 and anti-GQ1b antibodies bind to peripheral nerve and neuromuscular junctions 64,65 , and anti-GD1a antibodies bind to the nodes of Ranvier, paranodal myelin and neuromuscular junction 66,67,68 . Upon binding, the antibodies activate the complement cascade, resulting in formation of the membrane attack complex, disruption of sodium channel clusters at the node of Ranvier with disruption of nodal architecture 69 , and calcium influx and calpain-dependent neuronal and glial injury at the neuromuscular junction 70,71 .This injury can be ameliorated with complement inhibitors 72,73 .…”
mentioning
confidence: 99%